Three new POM-based coordination polymers with 1, 3, 5-tris(1-imidazolyl)benzene ligand: syntheses, structures and proton conductivity. Issue 8 (2nd February 2022) - Chen, Lin-Lin; Shi, Ya-Jie; Wu, Wen-Wen; Wang, Jia-Xin; Li, Ya-Min; Bai, Yan; Dang, Dong-Bin
Abstract : Three POM-based coordination polymers with 1, 3, 5-tris(1-imidazolyl)benzene have been synthesized. 1 exhibits a rare 3, 6-connected pyr topology; 2 and 3 reveal 3D hydrogen-bonded structures with good proton conductivity. Abstract : Three new POM-based coordination polymers, [Cu(timb)2 (W6 O19 )] n (1 ), [Zn3 (Htimb)2 (H2 timb)2 (H2 O)2 (ZnW12 O40 )2 ]·2H2 O n (2 ), and [Ni(Htimb)(H2 O)3 (H2 W12 O40 )0.5 ]·3H2 O n (3 ) (timb = 1, 3, 5-tris(1-imidazolyl)benzene), have been prepared under hydrothermal conditions. Compound 1 contains one 3D framework constructed by Cu II atoms and timb ligands with a rare 3, 6-connected pyr topology, while the polyoxoanions are situated in the cavities. For compound 2, the 3D framework is composed of a 2, 4-connected network (A) and hcb network (B) in the BBABB mode. The 1D chains of compound 3 are arranged into a 3D framework by a variety of hydrogen bonding interactions between the [H2 W12 O40 ] 6− polyoxoanions, coordinated water molecules and free water molecules. Magnetic data of compounds 1 and 3 show the presence of antiferromagnetic behavior. In addition, the highest proton conductivities of compounds 2 and 3 reach 2.32 × 10 −5 S cm −1 and 3.38 × 10 −5 S cm −1 at 358 K and 98% RH, respectively.